Coptisine, a protoberberine alkaloid, relaxes mouse airway smooth muscle via blockade of VDLCCs and NSCCs. Issue 2 (28th February 2020) - Wen, Nana; Xue, Lu; Yang, Yongle; Shi, Shunbo; Liu, Qing-Hua; Cai, Congli; Shen, Jinhua
Abstract: Background/Aims: Recently, effective and purified ingredients of traditional Chinese medicine (TCM) were extracted to play crucial roles in the treatment of pulmonary diseases. Our previous research focused on TCM drug screening aimed at abnormal airway muscle contraction during respiratory diseases. Coptisine, an effective ingredient extracted from bitter herbs has shown a series of antioxidant, antibacterial, cardioprotective and neuroprotective pharmacological properties. In the current study, we questioned whether coptisine could also participate in asthma treatment through relaxing abnormal contracted mouse airway smooth muscle (ASM). The present study aimed to characterize the relaxant effects of coptisine on mouse ASM and uncover the underlying molecular mechanisms. Methods: To investigate the role of coptisine on pre-contracted mouse ASM, a series of biological techniques, including force measurement and patch-clamp experiments were employed. Results: Coptisine was found to inhibit high K + or acetylcholine chloride (ACh)-induced pre-contracted mouse tracheal rings in a dose-dependent manner. Further research demonstrated that the coptisine-induced mouse ASM relaxation was mediated by alteration of calcium mobilization via voltage-dependent L-type Ca 2+ channels (VDLCCs) and non-selective cation channels (NSCCs). Conclusion: Our data showed that mouse ASM could be relaxed by coptisine via altering the intracellular Ca 2+ concentration through blocking VDLCCs and NSCCs, which suggested that this pharmacological active constituent might be classified as a potential new drug for the treatment of abnormal airway muscle contraction.